Customer perceptions of critical incidents in service encounters: the role restaurant employee's play in service recovery - Woznick, John M. (University of Wisconsin--Stout, 2018)
BelAir Cantina restaurants in southeastern Wisconsin have been growing at a rapid rate since their first restaurant opened in 2010. Continued success heavily relies on the experiences that each restaurant delivers to its current and future customers. More importantly, when a customer experiences a less than desirable dining experience, the way that the employees handle the situation can easily be the deciding factor whether those customers will be likely to recommend BelAir, return to BelAir, and how feel about BelAir Cantina. Customers of BelAir Cantina were surveyed to find out exactly what elements of their experience were dissatisfactory. In addition, they were questioned about how the staff of BelAir Cantina handled those specific situations. Of the respondents that answered, 50% indicated that service related issues were the root of their dissatisfaction. More troubling, was that over 50% of respondents stated that the employee was unaware of their dissatisfaction. These results prove the need for a training program that is designed to train frontline employees and managers how to effectively exceed guest expectations in the face of adversity. Recommendations for a training program are presented. Fortunately, 98% of survey participants responded that they would return to BelAir Cantina in the future.
Keywords: Restaurants; Customer services; Consumer satisfaction